Decrease in Plasma Levels of α-Synuclein Is Evident in Patients with Parkinson’s Disease after Elimination of Heterophilic Antibody Interference - Ishii, Ryotaro (PLoS One, 2015)
There is substantial biochemical, pathological, and genetic evidence that α-synuclein (A-syn) is a principal molecule in the pathogenesis of Parkinson disease (PD). We previously reported that total A-syn levels in cerebrospinal fluid (CSF), measured with the specific enzyme-linked immunosorbent assay (ELISA) developed by ourselves, were decreased in patients with PD, and suggested the usefulness of A-syn in CSF and plasma as a biomarker for the diagnosis of PD. After our report, a considerable number of studies have investigated the levels A-syn in CSF and in blood, but have reported inconclusive results. Such discrepancies have often been attributed not only to the use of different antibodies in the ELISAs but also to interference from hemolysis. In this study we measured the levels of A-syn in CSF and plasma by using our own sandwich ELISA with or without heterophilic antibody (HA) inhibitor in 30 patients with PD and 58 age-matched controls. We thereby revealed that HA interfered with ELISA measurements of A-syn and are accordingly considered to be an important confounder in A-syn ELISAs. HA produced falsely exaggerated signals in A-syn ELISAs more prominently in plasma samples than in CSF samples. After elimination of HA interference, it was found that hemolysis did not have a significant effect on the signals obtained using our A-syn ELISA. Furthermore, plasma levels of A-syn were significantly lower in the PD group compared with the control group following elimination of HA interference with an HA inhibitor. Our results demonstrate that HA was a major confounder that should be controlled in A-syn ELISAs, and that plasma A-syn could be a useful biomarker for the diagnosis of PD if adequately quantified following elimination of HA interference.